A review of research relating to food slicing in industrial applications. (March 2020) - Bremer, F.; Matthiesen, S.
Abstract: Food slicing in industrial applications is cutting foods into slices of predefined thickness. It has been subject to theoretical research, but experimental results are lacking. Experimental research on slicing is necessary to determine interrelations between design parameters, process parameters, food properties, and process quality. In this publication, a state of the art for slicing research is derived. Studies on rate and time dependence of food material properties, energy based descriptions of cutting as well as influences of blade geometry and sharpness were found in literature. Experimental conditions differ between cutting research and slicing. Hence, a direct transfer of knowledge from cutting research to slicing in industrial applications is not possible. Consequently, there is a need for experimental research on slicing to define ideal process conditions and blade designs. For this reason, we propose an approach to experimental setup for further research into slicing. Highlights: Influences of viscoelastic food properties on the cutting process found in research. Influences of blade properties on the cutting process found in research. Proposal for an experimental setup for slicing research.